2017
DOI: 10.1136/gutjnl-2016-313235
|View full text |Cite
|
Sign up to set email alerts
|

A microbial signature for Crohn's disease

Abstract: ObjectiveA decade of microbiome studies has linked IBD to an alteration in the gut microbial community of genetically predisposed subjects. However, existing profiles of gut microbiome dysbiosis in adult IBD patients are inconsistent among published studies, and did not allow the identification of microbial signatures for CD and UC. Here, we aimed to compare the faecal microbiome of CD with patients having UC and with non-IBD subjects in a longitudinal study.DesignWe analysed a cohort of 2045 non-IBD and IBD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
559
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 696 publications
(655 citation statements)
references
References 35 publications
37
559
2
6
Order By: Relevance
“…Comparative analysis using the weighted UniFrac distance indicated that the difference between CD and non-IBD controls was more marked than that between UC and non-IBD controls. These observations are compatible with the results of previous studies of fecal samples [33,34]. A focal alteration of the microbial structure within the inflamed mucosa of IBD has been reported previously [35].…”
Section: Discussionsupporting
confidence: 83%
“…Comparative analysis using the weighted UniFrac distance indicated that the difference between CD and non-IBD controls was more marked than that between UC and non-IBD controls. These observations are compatible with the results of previous studies of fecal samples [33,34]. A focal alteration of the microbial structure within the inflamed mucosa of IBD has been reported previously [35].…”
Section: Discussionsupporting
confidence: 83%
“…This was recently demonstrated by Pascal et al (14), who identified a unique microbial signature consisting of eight microbial markers for CD that was successfully validated in various different cohorts. However, when applied to a data set processed by a different methodological approach, their method achieved poor accuracy.…”
Section: Figmentioning
confidence: 88%
“…First, we used healthy children as controls, whereas clinicians need to discriminate IBD patients from those with other GI complaints or diseases. As for the cases, we decided, on the basis of our classification and perturbations results, to combine UC and CD patients into one IBD group, even though they were recently described as two distinct subtypes of IBD at the microbiota level (14). In addition, all of the IBD patients in our cohort were in the active state of the disease, so our model cannot be extrapolated to a remission state of IBD.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with IBD have a gut microbiome characterized by depletion or over‐abundance of specific taxa compared to healthy controls(Pascal et al ., 2017). Based on observations that Clostridia group IV and XIVa species in particular are less abundant in patients with IBD (Manichanh et al ., 2006), one such organism Faecalibacterium prausnitzii is being investigated as a candidate LBP for IBD, following up on promising findings in pre‐clinical colitis models (Sokol et al ., 2008).…”
Section: Microbiome Therapy Solution – Live Biotherapeuticsmentioning
confidence: 99%